Physical Model of Forming the Boundary Layer (Proceedings of Faculty of Civil Engineering, 2019)
The paper deals with the basic principles of forming the boundary layer in linear (2D) and spatial (3D) objects, along with the description and manner of their forming using physical models GUNT HM 133 and GUNT HM 152, which are an integral part of the hydro-technical laboratory of the Faculty of Civil Engineering, University in Rijeka. Firstly, the paper defines motion of liquid basics with Lagrange and Euler approach. The meaning of trajectories, streamlines, velocity vectors and acceleration, as well as their interdependence, were explained using textual formulations and graphic displays. The concept of angular deformities, suffered by particles of fluid due to movement, were also described. Furthermore, the paper describes the basic theoretical assumptions regarding formation of a boundary layer and three types of flow due to their formation. A part of paper also points to the importance of surface roughness and pressure gradient regarding the formation of the boundary layer. The legalitie, deremined for open channel systems, are also shown, because they correspond to the conditions of the applied physical modes. The paper describes the principles of work for the two stated physical models, the manner of preparing the experimental tests, and the conducted hydrodynamic analysis of fluid circulation on certain linear 2D structures (of circular, rectangular and aerofil shape) and spatial 3D structures (of cylindrical and aerodynamic shape).
Keywords: fluid motion; boundary layer; fluid flow around the body; physical model; HM 133 and HM 152